Penerapan Model Problem Based Learning pada Materi Kekongruenan dan Kesebangunan untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa SMP - Manalu, Agatha Friendsi; Murni, Atma; Saragih, Sehatta (Papanda, 2026)
This study aims to improve the mathematical communication skills of students in class IX-6 at SMP Negeri 3 Mandau through the implementation of the Problem Based Learning model on the topics of congruence and similarity. Based on interviews and observations, it was found that students faced difficulties in understanding problems, explaining mathematical ideas, and presenting mathematical models. This classroom action research was conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. The data collected included qualitative and quantitative data, which were analyzed to evaluate the improvement in students' mathematical communication skills. The results of the study indicate that the implementation of the Problem Based Learning model successfully enhanced student engagement and mathematical communication skills. The average KKM score of students increased from 31 in the initial test to 63 in cycle I, and reached 90 in cycle II. This improvement demonstrates that the Problem Based Learning model is effective in enhancing the learning process and improving students mathematical communication skills. Therefore, it can be concluded that the application of the Problem Based Learning model on the topics of congruence and similarity can enhance the quality of mathematics education in class IX-6 at SMP Negeri 3 Mandau.